Integrated in silico and experimental discovery of trimeric peptide ligands targeting Butyrylcholinesterase. (February 2023) - Mukherjee, Rudra Palash; Yow, Geok-Yong; Sarakbi, Samuel; Menegatti, Stefano; Gurgel, Patrick V.; Carbonell, Ruben G.; Bobay, Benjamin G.
Abstract: Butyrylcholinesterase (BChE) is recognized as a high value biotherapeutic in the treatment of Alzheimer's disease and drug addiction. This study presents the rational design and screening of an in-silico library of trimeric peptides against BChE and the experimental characterization of peptide ligands for purification. The selected peptides consistently afforded high BChE recovery (> 90 %) and purity, yielding up to a 1000-fold purification factor. This study revealed a marked anti-correlated conformational movement governed by the ionic strength and pH of the aqueous environment, which ultimately controls BChE binding and release during chromatographic purification; and highlighted the role of residues within and allosteric to the catalytic triad of BChE in determining biorecognition, thus providing useful guidance for ligand design and affinity maturation. Graphical Abstract: ga1 Highlights: Rational design and screening of trimeric peptides against BChE and the experimental characterization thereof. Peptides afforded high BChE recovery (> 90 %) and purity, yielding up to a 1000-fold purification factor. Identified the role of residues within and allosteric to the catalytic triad of BChE, thus providing useful guidance for ligand design.